2008
DOI: 10.1002/hon.876
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular large B‐cell lymphoma with FDG accumulation in the lung lacking CT/67gallium scintigraphy abnormality

Abstract: Intravascular large B-cell lymphoma (IVLBCL) is a rare lymphoma characterized by the presence of large tumour cells within the blood vessels. It has been considered that IVLBCL is a highly malignant disease with poor prognosis. However, it has been shown that a therapeutic effect resembling that of conventional B-cell lymphomas may be obtained with the application of systemic chemotherapy at the early stage of this disease. Although involvement in the lung is often detected at autopsy, early diagnosis is quite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…In several previous reports, TBLB was performed in patients with pulmonary IVL at an advanced stage (that is, in patients who had CT abnormalities) [6,7]. But there are only three cases (including our case) in which FDG-PET has proven useful in selecting a biopsy site for the early diagnosis of pulmonary IVL without a CT abnormality [8,9]. FDG accumulation is seen in other diffuse lung diseases such as tuberculosis, sarcoidosis, and interstitial lung diseases [10], but, owing to the rarity of pulmonary IVL, a specific pattern of tracer uptake in this disease is not well known.…”
Section: Discussionmentioning
confidence: 93%
“…In several previous reports, TBLB was performed in patients with pulmonary IVL at an advanced stage (that is, in patients who had CT abnormalities) [6,7]. But there are only three cases (including our case) in which FDG-PET has proven useful in selecting a biopsy site for the early diagnosis of pulmonary IVL without a CT abnormality [8,9]. FDG accumulation is seen in other diffuse lung diseases such as tuberculosis, sarcoidosis, and interstitial lung diseases [10], but, owing to the rarity of pulmonary IVL, a specific pattern of tracer uptake in this disease is not well known.…”
Section: Discussionmentioning
confidence: 93%
“…Follow-up with PET/CT showed resolution of the lung and spleen uptake after 2 cycles of chemotherapy. Kitanaka et al [ 8 ] reported bilateral lung uptake on FDG-PET in a patient with fever and splenomegaly who had negative 67 Ga scintigraphy and high-resolution chest CT scan. Follow-up PET showed resolution of the lung uptake after 6 cycles of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, chest CT revealed interstitial infiltrates, patchy consolidations, or ground glass opacities, but there have been only three cases in which chest CT showed no abnormal findings, as in our case. Despite the presence of dyspnea and hypoxia, chest radiography and CT may show no abnormal findings and might be nonspecific (3). Although the lung is not a common site used to make the diagnosis of IVLBCL, autopsies have revealed changes in the lung in approximately 60% of cases (4,8).…”
Section: Case Reportmentioning
confidence: 99%
“…Intravascular large B-cell lymphoma (IVLBCL) is a rare type of extranodal large B-cell lymphoma that is characterized by proliferation of lymphoma cells within the lumina of small blood vessels and capillaries, and it was recently listed as a rare subtype of diffuse large B-cell lymphoma in the World Health Organization (WHO) classification (1)(2)(3)(4)(5). Clinical symptoms occur when lymphoma cells proliferate within the lumina of the small vessels.…”
Section: Introductionmentioning
confidence: 99%